Some Fixed Point Results for TAC-Type Contractive Mappings. (29th February 2016) - Chandok, Sumit; Tas, Kenan; Hojat Ansari, Arslan
Abstract : We prove some fixed point results for new type of contractive mappings using the notion of cyclic admissible mappings in the framework of metric spaces. Our results extend, generalize, and improve some well-known results from literature. Some examples are given to support our main results.